Leveraging human touch in service interactions: lessons from hospitality. (3rd June 2019) - Solnet, David; Subramony, Mahesh; Ford, Robert C.; Golubovskaya, Maria; Kang, Hee Jung (Annette); Hancer, Murat
Abstract : Purpose: With the ever-increasing adoption of technology and automation radically changing the nature of service delivery, the purpose of this paper is to explore the role of human touch, introducing hospitable service as an enhancement for value creation in service organizations. Design/methodology/approach: Drawing on management, social sciences and hospitality literatures, a four-configuration model is presented to illustrate dimensions which arise from the confluence of different degrees of relationship orientation – shared mental models held by the host organization (self- or other-oriented), and guests' service preferences (transactional or relational). Findings: A theoretically grounded model of configurations resulting from variations on three key dimensions is offered. These are: employee organization relationships – social exchange processes governing the interactions between employees and their employers; HRM systems – internally consistent combinations of HR practices; and tech-touch trade-off – prioritization of technology vs employees to deliver services. Research limitations/implications: Embedding hospitable service as a construct to support the leveraging of human touch in service organizations opens up new research opportunities including avenues to further conceptualize the nature and dimensions of hospitable service. Future research that supports further understanding about the role of human touch and value creation in service organizations is proposed. Practical implications: Through the value-enhancing capability of human in the service encounter, firms can be enabled to accurately position themselves in one of the four relational configurations on offer and then identify opportunities for managers to leverage human touch to combat the diminishing role of the human touch in a technology-ubiquitous service context. Originality/value: This is among the first papers to explore the influence of technology on the degree of human touch in the interface between hospitality employee and customer, and to develop a configuration model through which researchers and practitioners can operate during this declining era of human to human service interactions.